Fulfillment of Patient Expectations at Two Years After Elective Foot and Ankle Surgery. Issue 4 (16th October 2019) - Henry, Jensen K.; Roney, Andrew; Hummel, Amelia; Cody, Elizabeth; Ellis, Scott
Category: Ankle, Ankle Arthritis, Bunion, Hindfoot, Lesser Toes, Midfoot/Forefoot, Sports, General foot/ankle elective procedures, outcomes Introduction/Purpose: The setting and fulfillment of expectations represent a unique aspect of patient-reported outcomes that is closely associated with satisfaction. Within foot and ankle surgery, patients may expect improvement in pain, mobility, shoe wear, and function in daily life, whether in basic activities or exercise/sports. Within foot and ankle surgery, a 23-item expectation survey has been developed based on patient responses and validated in patients undergoing elective surgery. However, to date, postoperative fulfillment of expectations has not been reported. This study aimed to describe overall rates of expectation fulfillment as well as fulfillment among specific domains. We hypothesized that patients would have the most improvement in pain and ambulation items, with greater rates of unfilled expectations for generalized items like improving confidence and returning to normal. Methods: This is a single-center study of adult patients undergoing elective foot/ankle surgery with 2-year follow-up. Demographic and clinical data were collected along with pre/postoperative Foot and Ankle Outcomes (FAOS) scores. Preoperatively, patients completed the expectations survey, citing the amount of improvement anticipated for each item using Likert-style responses. At 2 years postoperatively, patients repeated the survey, responding with the amount of improvement actually achieved. The total scores for the preoperative and postoperative surveys were used to create a ratio representing the proportion of expectations fulfilled (<1: fulfilled somewhat; 1: fulfilled as expected; >1: expectations surpassed), which was analyzed with descriptive statistics. Responses for each item (pre/postoperatively) were also assessed. Responses of "moderate, " "a lot, " or "complete" were considered fulfilled, while "little" or "no" indicated not fulfilled. FAOS scores were compared from baseline to follow-up using paired t-tests. Results: There were 271 patients (mean age 55.4, BMI 27.5, 65% female). Most common diagnoses were hallux valgus (25%), flatfoot (11%), hallux rigidus (11%), ankle arthritis (10%), and chronic tendon injury (9%). Patients had significant improvement in all FAOS domains (P<0.001). Mean proportion of expectations fulfilled was 1.15 (median 1.07, range 0-10), indicating surpassed expectations. Patients averaged complete fulfillment of 9 expectation items. Expectations were surpassed in 56%, met in 4%, and partially or not fulfilled in 41%. Rates of fulfillment were highest for ambulation distance, improving confidence, going back to normal, and preventing foot/ankle problem from getting worse, but did not match the level of expected improvement. Conversely, expectations were surpassed for ability to commute/drive, decreased reliance on pain medication, and participation in social/ activities. Conclusion: Overall, most patients had preoperative expectations that were met or surpassed. Though the proportion of expectations fulfilled exceeded 1, the rates of fulfillment for the most commonly cited items, especially more generalized items, were lower than expected. Improvement in ambulation ability (distance, speed, agility on uneven ground) was also lower than expected. Patients had greater improvement than expected in other functional domains (commute, social and household activities) and pain. These results may help guide appropriate management of expectations both pre and postoperatively. Future studies should assess fulfillment in the setting of specific pathologies and surgeries to better educate patients preoperatively.